Bioinformatics analysis of genes associated with the patchy-type alopecia areata: CD2 may be a new therapeutic target - Shi, Jiaxiao; Peng, Peng; Liu, Weixiao; Mi, Peng; Xing, Cong; Ning, Guangzhi; Feng, Shiqing (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc, Czechoslovakia, 2020)
Alopecia areata (AA) is mainly a T cell-medicated autoimmune disease with non-scarring hair loss and limited treatment options. Of these, the patchy-type alopecia areata (AAP) is the most common and relatively easy to treat due to smaller areas of the scalp affected. To understand the pathogenesis of AAP and explore the therapeutic target, we focus on the molecular signatures by comparing AAP and normal subjects. The gene expression profile (GSE68801) was obtained from Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) were identified between AAP patients and normal controls using the GEO2R. Then the Gene ontology (GO) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis and Protein-Protein interaction (PPI) network analysis were performed for DEGs. A total of 185 DEGs were identified, including 45 up-regulated genes and 140 down-regulated genes. The up-regulated DEGs were related to the immune response and chemokine signaling pathway. Meanwhile, down-regulated DEGs were enriched in keratin filament and intermediate filament. Subsequently, the top 10 hub genes were picked out in the PPI network, among them, CD2 showed the highest connectivity degree and central roles. Our data suggest that the CD2 may be a new therapeutic target for AAP. Further study is needed to explore the value of CD2 in the treatment of alopecia areata.